2020
DOI: 10.7717/peerj.9537
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of stool-based tests for mucosal healing among Taiwanese patients with ulcerative colitis: a retrospective cohort analysis

Abstract: Background/Purpose Over the past two decades, ulcerative colitis (UC) has emerged in the Asia Pacific area, and its treatment goal has shifted from symptom relief to endoscopic remission. Endoscopy is the gold standard for the assessment of mucosal healing; however, it is an invasive method. Fecal calprotectin (FC) is a non-invasive stool-based inflammatory marker which has been used to monitor mucosal healing status, but it is expensive. By contrast, the immune fecal occult blood test (iFOBT) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Food and medication, as well as blood from dietary sources or upper GI bleeding, can result in a positive test[ 20 ]. When compared to FC in a retrospective analysis in UC patients, iFOBT showed higher sensitivity and specificity for assessing MH (80.6% and 100% vs 74.1% and 84.2%, respectively)[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Food and medication, as well as blood from dietary sources or upper GI bleeding, can result in a positive test[ 20 ]. When compared to FC in a retrospective analysis in UC patients, iFOBT showed higher sensitivity and specificity for assessing MH (80.6% and 100% vs 74.1% and 84.2%, respectively)[ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of NAFLD has seen a rapid increase in the Asian population in the past decade [ 7 , 25 ], with the highest prevalence in Iran (64.29%) and the lowest in Taiwan (30.79%) [ 7 ]. During the same period, the incidence of IBD has increased worldwide, particularly in the Asia-Pacific region [ 1 , 2 ]. Our recent national cohort study in Taiwan reported a six-fold increase in the prevalence of IBD over the past 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD, including ulcerative colitis [UC] and Crohn's disease [CD]) is a chronic inflammatory disease affecting the gastrointestinal tract that has seen increased incidence and prevalence in Asia in the 21st century [1][2][3][4]. Non-alcoholic fatty liver disease (NAFLD) is becoming the most common chronic liver disease in the world, surpassing chronic hepatitis B [5] and hepatitis C [6] and affecting 22.28%-51.04% of the Asian population [7].…”
Section: Introductionmentioning
confidence: 99%
“…From January 2019, patients diagnosed with IBD, including UC or CD, received care in the hospital from a dedicated IBD nurse (TSH), who helped in reviewing patients’ clinical history and symptom, educating patients about the disease, and assessing the effects and/or side effects of treatment during each outpatient clinic visit. [ 12 ] The data in this analysis were reviewed by TSH and HHY. This study was approved by the institutional review board of Changhua Christian Hospital (approval number: CCH IRB 190814).…”
Section: Methodsmentioning
confidence: 99%